LAND DEGRADATION ASSESSMENT, IN THE PERI-URBAN AREA OF KADUNA METROPOLIS, NIGERIA - Adewuyi Taiye Oluwafemi (Indonesian Journal of Geography, 2009)
This study assessed land degradation in the peri-urban area of Kaduna metropolis from the perspective of land use and land cover with the aim of ascertaining the role of these variables and to suggest on how to manage their existing nature and characteristic. Random sampling method was used to collect data from field observation, measurement and semi-structured interview which are summarized and analyzed using descriptive statistics and presented in the form of tables and photographs. The results indicated that the existing nature and characteristic of land use and land cover cannot be exonerated from contributing to ongoing land degradation in the area for the following reasons: first, 6% of the area is already degraded, second, low average values for surface cover index (12.7%), leaf cover index (11.4%) and tree density (101 per 25,000m2), third, lost of vegetation biodiversity, fourth, absent of adequate conservation techniques to reduce the effects of crop farming and animal husbandry and lastly, evidence of problems already created by soil mining and refuse dumping. The situation in the study area calls for adequate land use and land cover planning, monitoring and management.